A call to greater inclusion of gerodontology in the dental curriculum: A narrative review. (2nd December 2018) - Nilsson, A; Young, L; Croker, F
Abstract: Aim: This literature review explores the need for greater prominence of gerodontology in the undergraduate dental curriculum, focusing on the significance of gerodontology for dental students on clinical placements. Background: As Australia's population ages the number of dentate older people is increasing. An assessment of the dental profession's preparedness, including that of future providers, is needed to ensure that this public health issue is addressed. Methods: A database search was performed in MEDLINE (Ovid), CINAHL and JCU OneSearch. Of the 41 articles identified, 31 were selected for review using a narrative approach. Discussion: Of the 31 articles reviewed, 12 were Australian, 9 North American and 5 European. Five overarching themes were identified, including preparedness for residential aged care facilities; barriers to oral health services provision; attitudes to aged care; gerodontology as part of a dental school curriculum and service‐based learning. Conclusion: There are differences in the gerodontology curricula of dental schools, with a wide variation of clinical exposure to older patients. There is evidence that exposure to gerodontology curriculum prior to treating older people may help dental students feel more prepared for managing patients in aged care. The current marginal status of gerodontology in dental school curricula is in need of review.